Utilização de diferentes tipos de amidas como agentes crioprotetores para espermatozóides de garanhões - Medeiros, Antonio Sylvio Lopes de [UNESP] (2003)
The present work aimed to investigated several kinds of amides to freeze equine semen. Two ejaculates from 20 stallions of different breeds were used. All ejaculates with initial motility greater than 60 % were split and frozen in 0.5 ml French straws in a milk base extender (INRA 82) containing the different studied cryoprotectants. The post-thaw percentage of motility and other motility parameters wer evaluated using CASA .To evaluate cell viability fluorescent probes were used. Stains used were Carboxyfluorescein and propidium iodine (PI). The first experiment was designed to investigated the protective effect of 3 amides ; Dymethyl acetamide at 3 concentrations - 1, 3 and 5 % v/v; dymethyl formamide at 5% and methyl formamide at 5%. Differences on motion parameters between cryoprotectant treatments were determined by analysis of variance using SAS system. Utilization of amides significantly improved most of parameters evaluated when compared with Glycerol. Progressive motility evaluated by optical microscopy was higher (p< 0,0001) for semen that was frozen with MF 5% and DF5%. The progressive motility evaluated by CASA was higher for the MF 5 % and DA 3% groups. The electron microscopy evaluation showed that DA 5% and MF 5 % were superior in the ability to preserved the acrossomal integrity. The acrossomal status evaluated by fluorescence showed that the preservation was higher on the groups DA 5%, MF 5 % and DF5% (p<0.0001). On the second experiment the cryoprotective effect of two associations of glycerol (Gly) and dimethylformamide (DF) were tested ( Gly 3.5% + DF 1.5 % and DF 3.5% + Gly 1.5%)... (Complete abstract, click electronic address below).